Determining the Impact of Careful Application of Growth Management Policies and Sustainable Development on the Changing Marketing Environment - Al-Waely, Dina (Modern Perspectives in Economics, Business and Management Vol. 2, 2021)
The purpose of this study was to determine the impact of careful implementation of growth management policies and sustainable development on the changing marketing environment. Business exercises and the market environment are associated and depend on one another. The study took a descriptive analytical technique, with a questionnaire serving as the research tool.The questionnaire included three demographic variables and twenty-six items designed to assess the impact of careful implementation of growth management policies and sustainable development on the changing marketing environment. All Senior Managers who work at five-star hotels at the Dead Sea in Amman, Jordan, were included in the study population, which totaled (19) Senior Managers at (6) hotels, and the study sample comprised all (19) managers. The findings revealed that careful application of growth management policies has a statistically significant impact on the changing marketing environment, as well as that careful application of sustainable development has a statistically significant impact on the changing marketing environment. The analysis revealed that the means and standard deviations of the careful application of growth management policies fields were high, with the Attraction field coming first and the Expansion field coming last. Other findings revealed thatthe total mean and standard deviation of the Coordination field were high, where it had a mean of (3.91) and a standard deviation of (0.51). From the standpoint of the analysis, the means and standard deviations of the sustainable development fields were high, with the Economic Dimension field coming first and the Environmental Dimension field coming last.